Plants for Toxicity Assessment: Second Volume 1991
DOI: 10.1520/stp19505s
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Pesticide Toxicity to Aquatic Plants: Recommendations for Test Species

Abstract: A literature review of pesticide toxicity to aquatic plants was conducted in order to arrive at a set of species for use in preregistration testing. Criteria used in the selection process were: (1) existing database; (2) interspecies variability in response to pesticides; (3) availability of well-characterized plant cultures; and (4) ease of culture. Freshwater and marine algae and freshwater and estuarine macrophytes were included in the study. Results showed that the three practical criteria [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
2
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 29 publications
0
36
2
1
Order By: Relevance
“…Thus, only a few data are available for the pesticide toxicity on riverine periphytic algal species (for example Larras et al, 2012). Moreover, it is well known that the sensitivity to pesticides differs markedly among species (van den Brink et al, 2006;Nagai et al, 2011), and a single specific indicator algal species cannot be representative of the whole algal assemblage (Freemark et al, 1990;Swanson et al, 1991). Therefore, toxicity data for multiple species should be obtained efficiently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, only a few data are available for the pesticide toxicity on riverine periphytic algal species (for example Larras et al, 2012). Moreover, it is well known that the sensitivity to pesticides differs markedly among species (van den Brink et al, 2006;Nagai et al, 2011), and a single specific indicator algal species cannot be representative of the whole algal assemblage (Freemark et al, 1990;Swanson et al, 1991). Therefore, toxicity data for multiple species should be obtained efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of pesticides on algae are generally analyzed by standard test methods (OECD, 2006), which require considerable labor for testing multiple species and is not suitable for periphytic species because of algal attachment to the surface of Erlenmeyer flasks (Swanson et al, 1991). Instead, Ishiahara et al (2006) showed the use of a microplate assay in which periphytic algae are attached to the bottom of a microplate.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the Lemnaceae family are ubiquitous, ecologically important, easily grown, and readily and reliably manipulated. Also, its value as a test species for toxicity assessment has been discussed worldwide, and it has been adopted as a test material in guidelines used for registration of agrochemicals (8). Given the wide distribution and ecological importance of duckweed, it is indispensable for aquatic risk assessment in determining its uptake and metabolic response to typical pesticide metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…To improve this situation, a species battery approach needs to be used in laboratory phytotoxicity tests where several taxonomically different algae are exposed to the test substance. Swanson et al (1991) provide a list of possible species. Aquatic macrophytes are used less frequently than algae in the toxicity tests.…”
Section: Aquatic Test Organismsmentioning
confidence: 99%